Bioactive substances of cyanobacteria and microalgae: Sources, metabolism, and anticancer - Bouyahya, Abdelhakim; Bakrim, Saad; Chamkhi, Imane; Taha, Douae; El Omari, Nasreddine; El Mneyiy, Naoual; El Hachlafi, Naoufal; El-Shazly, Mohamed; Khalid, Asaad; Abdalla, Ashraf N.; Goh, Khang Wen; Long, Chiau Ming *; et al. (Elsevier, 2024)
Cyanobacteria and microalgae contain various phytochemicals, including bioactive components in the form of secondary metabolites, namely flavonoids, phenolic acids, terpenoids, and tannins, with remarkable anticancer effects. This review highlights the recent advances in bioactive compounds, with potential anticancer activity, produced by cyanobacteria and microalgae. Previous in vitro investigations showed that many of these bioactive compounds exhibit potent effects against different human cancer types, such as leukemia and breast cancers. Multiple mechanisms implicated in the antitumor effect of these compounds were elucidated, including their ability to target cellular, subcellular, and molecular checkpoints linked to cancer development and promotion. Recent findings have highlighted various mechanisms of action of bioactive compounds produced by cyanobacteria and microalgae, including induction of autophagy and apoptosis, inhibition of telomerase and protein kinases, as well as modulation of epigenetic modifications. In vivo investigations have demonstrated a potent anti-angiogenesis effect on solid tumors, as well as a reduction in tumor volume. Some of these compounds were examined in clinical investigations for certain types of cancers, making them potent candidates/scaffolds for antitumor drug development.